IDENTIFYING SALIENT ISSUES IN INFORMATION AND COMMUNICATION TECHNOLOGY EDUCATION IN THE MUSLIM WORLD - Ahmad Faizuddin (CYBERSPACE: Jurnal Pendidikan Teknologi Informasi, 2017)
Information and communication technology (ICT) in education has been widely used in many schools and learning institutions all over the world. However, the use of ICT in the Muslim world to improve the teaching and learning process is still limited. Indonesia as the most populace Muslim community in the world for instance, still does not have sufficient computer or Internet access in most of learning centers. This poses many challenges particularly in education. Young Muslims nowadays are caught between modernity and tradition. ICT can lead a Muslim to an ambiguous modern lifestyle and at the same time prying integrity of their identity. In some ways, Muslim youngsters are adopting technology with the aim to distance themselves from older people and traditional practices. On the other hand, there are some who challenge Western models. How should ICT education develop within an increasingly digital technological world? This article mainly highlights salient issues of ICT education in the Muslim world and the challenges of Muslim identity in the Internet era. It also examines the impact of digital technology on education for Muslim students and synthesizes ICT education from the Islamic point of view. Finally, some recommendations are appraised accordingly.